Holocene environment changes around the Sara Us River, northern China, revealed by optical dating of lacustrine–aeolian sediments. (15th April 2016) - Zhao, Hui; Sheng, Yongwei; Li, Bo; Fan, Yuxin
Highlights: Quaternary sediments sequences exposed beside Sara Us River. Environment changes in Holocene around the river are revealed by OSL dating. Close sections in SUR valleys recorded complicated local environmental changes. Ages and elevations do not support a mega lake covering the study area. The Sara Us River meandering may cause the intricate environmental changes. Abstract: The Sara Us River is located along the boundary of the Mu Us Desert and the Chinese Loess Plateau in northern China. The river has cut down through Quaternary sediments creating 70–80 m deep valleys with thick lacustrine/aeolian sequences exposed. We applied optical stimulated luminescence on sediments from a Holocene section of aeolian sand/lacustrine deposits in the top of the river valley. The dating results show that a humid period existed from 7.1 to 2.0 ka ago as evidenced by two layers of peat and lacustrine sediments. However, compared to other published Holocene sections in the Sara Us River valleys close to the section under studying, the local environment experienced very complicated changes during the Holocene. All of the sections recorded a period with drought and/or cold before the Holocene at around 13 ka, and an episode of aridity after about 2 ka ago as evidenced by the layers of aeolian sand. However, the ages of the lacustrine and peat layers in these sections are substantially different. Geomorphological analysis by digital elevation models does not support the existence of a mega lake covering the study area at 2 ka. The intricate environmental changes may have been caused by the meandering of the Sara Us River. Environmental changes also strongly affected human migration in this area, which is documented by Chinese historical records.